2022
DOI: 10.1186/s12884-022-04419-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFD1 gene polymorphisms and maternal smoking with risk of congenital heart disease: a hospital-based case-control study

Abstract: Background MTHFD1 gene may affect the embryonic development by elevated homocysteine levels, DNA synthesis and DNA methylation, but limited number of genetic variants of MTHFD1 gene was focused on the association with congenital heart disease (CHD). This study examined the role of MTHFD1 gene and maternal smoking on infant CHD risk, and investigated their interaction effects in Chinese populations. Methods A case-control study of 464 mothers of CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Similarly, Wang et al [ 35 ] found that higher parity groups showed a decreased risk of isolated CHDs. Moreover, we found that mothers who reported having a lack of folic acid use, passive smoking during pregnancy, threatened abortion, maternal history of CHD, take medicine during the first trimester, assisted reproduction, infant with preterm birth have a higher prevalence of CHDs in offspring, these findings were also consistent with previous studies which suggested that mothers with these characteristics had an increased risk of having offspring with CHDs [ 12 , 14 , 36 38 ]. Furthermore, maternal history of internal diseases and hyperthyroidism were positively associated with higher risk for CHDs in offspring.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Wang et al [ 35 ] found that higher parity groups showed a decreased risk of isolated CHDs. Moreover, we found that mothers who reported having a lack of folic acid use, passive smoking during pregnancy, threatened abortion, maternal history of CHD, take medicine during the first trimester, assisted reproduction, infant with preterm birth have a higher prevalence of CHDs in offspring, these findings were also consistent with previous studies which suggested that mothers with these characteristics had an increased risk of having offspring with CHDs [ 12 , 14 , 36 38 ]. Furthermore, maternal history of internal diseases and hyperthyroidism were positively associated with higher risk for CHDs in offspring.…”
Section: Discussionsupporting
confidence: 91%
“…One study found maternal dietary factors and cystathionine beta synthase ( CBS ) gene variants (rs2851391, rs234714) interactions were significantly associated with risk of CHDs [ 51 ]. One study observed the interaction between maternal tobacco exposure and polymorphisms of the MTHFD1 gene including rs1950902, rs2236222, rs1256142, rs11849530 and rs2236225, was significantly associated with the risk of CHDs in offspring [ 52 ]. One study reported a significantly positive interaction between maternal folic acid supplementation and genetic variation at rs828858 of MTHFD2 for the risk of CHDs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, professionally trained investigators conducted face-to-face interviews to collect data. Based on our previous studies [ 18 , 26 ], the following covariables were used as confounding factors for subsequent analysis: socio-demographic characteristics (residence, maternal age of pregnancy, pre-pregnancy body mass index (BMI), and child sex), adverse pregnancy history (spontaneous abortion, stillbirth, premature delivery, and low birth weight (LBW)), pre-pregnancy chronic diseases (diabetes), history of pregnancy complications (gestational diabetes and gestational hypertension), and maternal perinatal lifestyle (antibiotic use, perinatal cold, fever, smoking, exposure to second-hand smoke, and drinking). In China, every pregnant woman possesses a “Perinatal Health Handbook” (PHCH), which contains her pregnancy and personal information.…”
Section: Methodsmentioning
confidence: 99%
“…Disruptions in the function of MTHFD1 and MTHFD2 genes, caused by mutations or abnormalities, can interfere with folic acid metabolism and have adverse effects on cellular biological processes [ 17 ]. Previous studies suggested that genetic variations in MTHFD1 and MTHFD2 genes may contribute to the occurrence and development of CHD [ 18 , 19 , 20 ]. Notably, a study using a mouse model observed that deficiency in MTHFD1 synthetase was associated with a higher incidence of CHD, particularly ventricular septal defects (VSD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation